COMPARISON OF LABOR ANALGESIC EFFECTIVENESS OF PROGRAMMED INTERMITTENT EPIDURAL BOLUS USING ROPIVACAINE AT DIFFERENT VOLUMES COMBINED WITH FENTANYL (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate and compare the effectiveness of labor analgesia using programmed intermittent epidural bolus with Ropivacaine 0.1% combined with Fentanyl 2 µg/ml at 3 different volumes of Ropivacaine bolus (6 ml, 8 ml, and 10 ml/60 minutes).Method: A randomized controlled clinical trial was conducted from March 2025 to September 2025 at the Delivery Department, Hanoi Obstetrics and Gynecology Hospital, including 90 nulliparous women with term pregnancy, cephalic presentation, ASA physical status I-II. Participants were randomly assigned into 3 groups (30 pregnant women/group) to receive bolus doses of 6 ml, 8 ml, or 10 ml via a Terumo syringe pump. Analgesic effectiveness was assessed by VAS scores, number of rescue doses, maternal satisfaction, uterine contractions, labor progression, and motor block Bromage score. Data were analyzed using SPSS 20.0 software, with statistical significance set at p < 0.05.Results: VAS scores decreased rapidly in all groups, reached its lowest level at 1 hour 10 minutes post-anesthesia (1.3-1.4 points). At 1 hour 40 minutes post-anesthesia, the 10 ml group showed the best analgesic effect (VAS 2.2 ± 0.4; p = 0.00). No rescue doses were required in the 10 ml group, while the 6 ml group had the highest mean number of rescue doses (0.30 ± 0.70; p = 0.03). Motor function was preserved in 96.7% of women (Bromage 0). Uterine contractions and labor progression remained physiological, with no significant differences among groups (p > 0.05). The highest rate of very satisfied women was observed in the 10 ml group (33.3%), compared to 23.3% in the 8 ml group and 3.3% in the 6 ml group (p = 0.01).Conclusion: Programmed intermittent epidural bolus with Ropivacaine 0.1% combined with Fentanyl 2 µg/ml is safe and effective for labor analgesia. A bolus volume of 10 ml/60 minutes demonstrated superior analgesic efficacy, stability, and maternal satisfaction compared to 8 ml and 6 ml.
Keywords: Labor, epidural analgesia, PIEB, Ropivacaine, Fentanyl.